Anabolic androgenic steroids intake and its impact on male reproductive system - systematic review - Maja Mielczarek; Paulina Sroczyńska; Jan Sroczyński; Julia Lachowska; Karolina Senior; Jerzy Smandek (Quality in Sport)
Anabolic-androgenic steroids (AAS) are a significant lifestyle factor in infertility and are often used to enhance physical performance and appearance. Endogenous AAS regulate male sex organ development and secondary characteristics. Commonly used AAS include testosterone esters like undecanoate and enanthate, as well as nandrolone esters, testosterone cypionate, and testosterone propionate—along with nandrolone esters, such as nandrolone decanoate and nandrolone phenylpropionate, stanozolol and methandrostenolone (also known as methandienone). AAS bind to androgen receptors, promoting muscle growth by increasing protein synthesis and promoting the growth hormone-insulin-like growth factor 1 axis. AAS are commonly administered via intramuscular injection or oral ingestion. Injectable forms of AAS have extended half-life due to esterification, while oral AAS face reduced bioavailability because of first-pass metabolism. Adverse effects of AAS include cardiovascular, endocrine, neuropsychiatric and dermatological issues. AAS usage has a huge impact on male fertility. Anabolic androgenic steroids intake can result in suppressing  gonadotropins, leading to reduced sperm concentration, testicular dysfunction and hypogonadism, which can lead to decreased libido and erectile dysfunction. While some effects on fertility may be reversible, recovery timelines vary.